Social Technology Enhancing the Town Centre Management Attractiveness - Caboni, Federica; Bruni, Roberto (Journal of Technology Management & Innovation, 2018)
The article describes the social technology’s role in the TCM attractiveness from the retailers’ perspective. The exploratory research experience in Sweden during different periods between 2012 and 2016 includes contributions of the literature, direct interviews and analysis of the TCM’s websites. The state-of-the-art of social commerce perception by managers and retailers is defined, and specific evidences are given through research. An interpretation of the concept of attractiveness of the TCM is presented to explain how social commerce could affect this property. Dissonance between opinions and statements of TCM stakeholders are discussed, and the will to use social commerce to increase opportunities for TCM is, in general, declared by retailers, but it is not realized in practice in management activities. A comparative empirical exploration between different countries could be conducted in future. This paper explores the actual situation in the use of website sustaining that the social commerce and the social networks are able to go beyond the supporting of commerce activity and they are able to support the TCM attractiveness and place attachment.